1995
DOI: 10.1074/jbc.270.34.19908
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Antagonizes Serotonin and Growth Factor-induced Mitogen-activated Protein Kinase Activation in Bovine Tracheal Smooth Muscle Cells

Abstract: We examined the effects of the bronchoconstrictor agonists serotonin (5-hydroxytryptamine; 5-HT) and histamine on mitogen-activated protein (MAP) kinase activation in cultured bovine tracheal myocytes. Kinase renaturation assays demonstrated activation of the 42- and 44-kDa MAP kinases within 2 min of 5-HT exposure. MAP kinase activation was mimicked by alpha-methyl-5-HT and reduced by pretreatment with either phorbol 12,13-dibutyrate or forskolin, suggesting activation of the 5-HT2 receptor, protein kinase C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
50
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 31 publications
9
50
2
Order By: Relevance
“…Various diverse stimuli have now been demonstrated to increase the proliferation of airway smooth muscle cells in cell culture, and have been reviewed in detail elsewhere [13,47,48]. Broadly, the substances now implicated in mitogenesis of airway smooth muscle, in addition to the action of serum itself (discussed in [49]), include pro-inflammatory mediators (histamine [46], 5-hydroxytryptamine (5-HT) [50], phenylephrine [51], tachykinins [52], endothelin (ET)-1 [53±56] and leukotriene D 4 [57]), several inflammatory cell-and plasma-derived enzymes (a-thrombin [58], tryptase [59], b-hexosaminidase and b-glucuronidase [60]), polypeptide growth factors (platelet-derived growth factor (PDGF) [61], epidermal growth factor (EGF) [62], fibroblast growth factor-2 (FGF-2) [63] and insulin-like growth factors (IGFs) [64]) and thromboxanes [65]. Pro-inflammatory cytokines (interleukin-1b [66], interleukin-6 [67], and tumour necrosis factor-a [68]) also induce a proliferative response in airway smooth muscle, which is revealed only under conditions of cyclo-oxygenase inhibition [69], in which the production and action of inhibitory prostanoids such as prostaglandin E 2 is limited.…”
Section: Mediators Of Airway Smooth Muscle Proliferationmentioning
confidence: 99%
See 4 more Smart Citations
“…Various diverse stimuli have now been demonstrated to increase the proliferation of airway smooth muscle cells in cell culture, and have been reviewed in detail elsewhere [13,47,48]. Broadly, the substances now implicated in mitogenesis of airway smooth muscle, in addition to the action of serum itself (discussed in [49]), include pro-inflammatory mediators (histamine [46], 5-hydroxytryptamine (5-HT) [50], phenylephrine [51], tachykinins [52], endothelin (ET)-1 [53±56] and leukotriene D 4 [57]), several inflammatory cell-and plasma-derived enzymes (a-thrombin [58], tryptase [59], b-hexosaminidase and b-glucuronidase [60]), polypeptide growth factors (platelet-derived growth factor (PDGF) [61], epidermal growth factor (EGF) [62], fibroblast growth factor-2 (FGF-2) [63] and insulin-like growth factors (IGFs) [64]) and thromboxanes [65]. Pro-inflammatory cytokines (interleukin-1b [66], interleukin-6 [67], and tumour necrosis factor-a [68]) also induce a proliferative response in airway smooth muscle, which is revealed only under conditions of cyclo-oxygenase inhibition [69], in which the production and action of inhibitory prostanoids such as prostaglandin E 2 is limited.…”
Section: Mediators Of Airway Smooth Muscle Proliferationmentioning
confidence: 99%
“…MEK-1 activates both p44 ERK1 and p42 ERK2 by direct phosphorylation of tyrosine and threonine residues. In bovine airway smooth muscle, ERK activation is induced by a wide variety of stimuli, including PDGF, EGF, IGF-1, 5-HT [50,74], bradykinin [75], a-thrombin [75,76], ET-1 [56,76] and hydrogen peroxide [77]. Several independent groups have reported that the duration of ERK activation is critical for transduction of the mitogenic stimulus.…”
Section: Mediators Of Airway Smooth Muscle Proliferationmentioning
confidence: 99%
See 3 more Smart Citations